The Influence of Rural Road Infrastructure on Rice Crop Productivity in Indonesia: Road Infrastructure and Rice Productivity (Journal of Tropical Rural Development, 2024)
Background and purposes - Infrastructure development plays a critical role in enhancing agricultural productivity, particularly in Indonesia, where the agricultural sector is a cornerstone of the economy. This study investigates the impact of road infrastructure—specifically road length and road stability—on rice productivity in Indonesia. The purpose of this research is to analyze how road infrastructure affects agricultural outcomes and to provide insights into the relationship between infrastructure development and rice production efficiency. Methodology - The study employs a quantitative methodology using panel data regression analysis. Data were collected from 31 provinces over a 10-year period (2013–2022), focusing on key variables such as road length, road stability, and rice productivity. This approach integrates cross-sectional and time-series data to offer a comprehensive analysis of infrastructure’s role in agricultural performance. Findings - The findings reveal that road length has a significant and positive effect on rice productivity, with every 1% increase in road length corresponding to a 124.1819 unit increase in rice output. However, road stability did not show a significant effect on productivity. These results suggest that improved connectivity, facilitated by longer road networks, is a critical factor in enhancing farmers' access to agricultural inputs and markets, thereby boosting productivity. Implications - The implications of this study are clear: prioritizing road infrastructure development, particularly in rural and agricultural areas, is essential for improving agricultural productivity and ensuring food security. Enhanced road networks reduce logistical costs, improve farmers' access to essential resources, and ultimately contribute to economic development and poverty alleviation in Indonesia. This research provides valuable insights for policymakers seeking to strengthen infrastructure to support agricultural growth.